The effect of the Application of Restorative Justice System on the settlement of Criminal Cases in Indonesia in the perspective of Customary Law - Medan, Karolus Kopong; Lewokeda, Kornelia Melansari Deran; Rumalean, Zonita Zirhani; Rois, Nur (PT. Anagata Sembagi Education, 2025)
The application of the Restorative Justice System (RJS) in Indonesia offers an alternative approach to resolving criminal cases by prioritizing reconciliation, victim recovery, and offender accountability. This study explores the impact of RJS on the resolution of criminal cases from the perspective of customary law, which plays a significant role in many Indonesian communities. By integrating customary practices into the formal legal framework, restorative justice fosters community involvement and strengthens social harmony. The research highlights successful case studies from regions such as Papua, Aceh, and Bali, demonstrating the effectiveness of customary law in promoting peaceful conflict resolution. However, challenges such as legal inconsistencies, limited public awareness, and lack of mediator training persist. The study concludes with policy recommendations to enhance the synergy between customary law and the national legal system, aiming to build a more inclusive and equitable criminal justice process in Indonesia.